From imperial revenants to Cold War victims: 'red repatriates' from the Soviet Union and the making of the new Japan, 1949–1952. Issue 4 (2nd October 2017) - Muminov, Sherzod
Abstract: When over half a million former Imperial Japanese Army soldiers returned home from long captivity in Soviet labour camps in the late 1940s, they brought back more than their memories of hardship and humiliation. In post-war society, the Siberian returnees were the uncomfortable remnants of the failed Japanese Empire; yet it was their brush with the communist enemy that caused suspicion and dragged them into the domestic political struggles. In this article, I use the experiences of Siberian internees as a lens to reconsider Japan's formative post-war decade, when the onset of the Cold War eclipsed the inconvenient legacies of empire.